REVIEW OF OCCURRENCES AND CARBON ISOTOPE GEOCHEMISTRY OF OXALATE MINERALS: IMPLICATIONS FOR THE ORIGIN AND FATE OF OXALATE IN DIAGENETIC AND HYDROTHERMAL FLUIDS - Hofmann B.A.; Bernasconi S.M. (My University, 1998)
The known occurrences of oxalate minerals in deep diagenetic and hydrothermal environments are reviewed and new carbon isotope results are presented that cover, together with previously published data, 22 of 37 known diagenetic (n=22) and hydrothermal (n=15) oxalate occurrences. The very large range of observed δ13C compositions of solid oxalates, -31.7 to 33.7%% (VPDB), is largely independent of the carbon isotope signature of associated organic carbon and can be best explained by isotope fractionation processes during oxalate formation and breakdown. Within single deposits, the range in δ13C is rather limited. Diagenetic whewellites are, on the average, nearly 12%% heavier than hydrothermal ones. Isotopically heavy oxalate minerals appear to be preferentially associated with Al-phases, possibly indicating Al deposition as a result of the destruction of oxalate complexant. Oxalates from near-surface and biological sources are enriched in 13C by 1 to 6%% relative to the bulk organic matter. The heterogeneity of oxalate mineral δ13C reflects the low stability of dissolved oxalate due to thermal decarboxylation, oxidation and microbial degradation. The calcium oxalate whewellite is stable over geological periods of time at temperatures of at least 68°C (highest in situ temperature of whewellite occurrence) and provides easy access to the isotopic signature of an organic constituent of palaeofluids. The extreme variability of the C isotope signature of oxalate demonstrates that isotope fractionation during organic acid breakdown is a mechanism that must be taken into consideration in the interpretation of both very 13C-depleted and enriched natural carbon.
Keywords: OXALATE; CARBON ISOTOPES; WHEWELLITE; DIAGENESIS; ORGANIC ACIDS